Cluster headache-like attack as an opening symptom of a unilateral infarction of the cervical cord: Persistent anaesthesia and dysaesthesia to cold stimuli. Issue 3 (1st March 1999) - de la Sayette, Vincent; Schaeffer, Stéphane; Coskun, Oguzhan; Leproux, François; Defer, Gilles
Abstract : A 54 year old man experienced excruciating left retro-orbital pain with lacrimation and redness of the eye representative of a cluster headache attack. This was followed by left hemiparesis with plegia of the lower limb and left Horner's syndrome. Five days later the hemiparesis recovered while the patient developed hypoanaesthesia to cold stimuli that evoked painful burning dysaesthesia on the right side below the C4 level. MRI disclosed a discrete infarct in the left lateral aspect of the cord at C2 level concomitant to a left vertebral artery thrombosis. This limited infarct and the clinical symptoms suggest a hypoperfusion in the peripheral arterial system of the left hemicord, supplied both by the anterior and posterior spinal arteries. Cluster headache-like attack and persistent dysaesthesia to cold stimuli are discussed respectively in view of the central sympathetic involvement and partial spinothalamic system dysfunction.